Information acquisition system of multipoint soil surface height variation for profiling mechanism of seeding unit of precision corn planter - Zhang, Bo; Zhang, Wei; Qi, Liqiang; Fu, Haiba; Yu, Lijuan; Li, Rui; Zhao, Yue; Ma, Xinxian (International Journal of Agricultural and Biological Engineering, 2018)
The emergence rate and vitality of maize are directly affected by the sowing depth, and the uniformity of this depth is an important performance indicator of a planter, while the effective soil surface height information acquisition is the prerequisite for ensuring the accuracy of sowing depth control. The soil surface height variation acquisition system of a precision corn planter often produces profiling errors when performing active profiling due to interference from ground debris. In this study, a multipoint soil surface height variation information acquisition system was investigated, which consists of a ranging sensor group and a microcontroller unit (MCU) using a data comparison and screening method. The structure and specifications of the ranging sensors were determined according to the soil surface height variation and debris size, and a nonessential profiling control program was developed. Performed tests on the information acquisition system indicated that the measurement accuracy of the system was 3 mm, and when advancing at a speed of 8 km/h, the accuracy of the profiling decision and the system stability were 97.1% and 94.1%, respectively, indicating that the system was capable of nonessential profile control. The designed ranging system could provide a reference for the design of a ground information acquisition system of precision planters with an active profiling mechanism. Keywords: corn, precision planter, information acquisition system, seeding unit, profiling mechanism, active profiling, soil surface height variation DOI: 10.25165/j.ijabe.20181106.4037 Citation: Zhang B, Zhang W, Qi L Q, Fu H B, Yu L J, Li R, et al. Information acquisition system of multipoint soil surface height variation for profiling mechanism of seeding unit of precision corn planter. Int J Agric & Biol Eng, 2018; 11(6): 58–64.